Effect Of Family Ownership In The Relationship Between Corporate Governance Mechanism And Earning Management - Zirman Zirman; Vera Oktari; Fitri Humairoh; Jonnius Jonnius (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Financial statements are the basis for many parties' decision-making in describing the condition of a company, so companies must present the quality of the information therein. This study examines the relationship between corporate governance mechanisms and earning management and how family ownership influences this relationship. This empirical study uses companies on the Kompas 100 index from 2015 to 2019 to be tested using Generalized Least Squares(GLS). This study finds that the board of commissioners affects earnings management, and family ownership strengthens the role of the board of commissioners in suppressing earnings management. This study strengthens the literature on family ownership in companies. Internal auditors can consider the implication of increasing the effectiveness of internal audits to produce more accurate quality financial reports. In addition, the implications of this study also recommend restructuring the internal audit function, especially its role in management and governance, to be more objective and also impartial.